2021
DOI: 10.1016/j.jhazmat.2020.123916
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and prediction of water uptake by soot deposited on ventilation filters during fire events

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The droplet formation of water-insoluble particles has been previously described with adsorption activation models (Hatch et al, 2012;Kumar et al, 2009;Lintis et al, 2021;Malek et al, 2022;Navea et al, 2017;Pajunoja et al, 2015;Tang et al, 2016). Brunauer, Emmett, and Teller adsorption isotherm models are typically applied for multilayer adsorption analysis of water uptake on clays (Hatch et al, 2012) and fly ash (Navea et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The droplet formation of water-insoluble particles has been previously described with adsorption activation models (Hatch et al, 2012;Kumar et al, 2009;Lintis et al, 2021;Malek et al, 2022;Navea et al, 2017;Pajunoja et al, 2015;Tang et al, 2016). Brunauer, Emmett, and Teller adsorption isotherm models are typically applied for multilayer adsorption analysis of water uptake on clays (Hatch et al, 2012) and fly ash (Navea et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Brunauer, Emmett, and Teller adsorption isotherm models are typically applied for multilayer adsorption analysis of water uptake on clays (Hatch et al, 2012) and fly ash (Navea et al, 2017). Lintis et al (2021) applied the Dubinin-Serpinsky model for soot and concluded that nucleation occurred at oxidized and hydrophilic surface sites on the soot. Pajunoja et al (2015) measured the TK hygroscopicity for SOA and demonstrated that the droplet growth of organic compounds with low O : C ratio was an adsorption-dominated process for both sub-and supersaturated water vapor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The droplet formation of water-insoluble particles has been previously described with adsorption activation models (Hatch et al, 2012;Kumar et al, 2009;Lintis et al, 2021;Malek et al, 2022;Navea et al, 2017;Pajunoja et al, 2015;Tang et al, 2016). Brunauer, Emmett, and Teller (BET) adsorption isotherm models are typically applied for multilayer adsorption analysis of water uptake on clays (Hatch et al, 2012) 45 and fly ash (Navea et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Brunauer, Emmett, and Teller (BET) adsorption isotherm models are typically applied for multilayer adsorption analysis of water uptake on clays (Hatch et al, 2012) 45 and fly ash (Navea et al, 2017). Lintis et al, 2021 applied the Dubinin-Serpinsky model for soot and concluded that nucleation occurred at oxidized and hydrophilic surface sites on the soot. Pajunoja et al measured the TK hygroscopicity for SOA and demonstrated that the droplet growth of organic compounds with low O:C ratio was an adsorption-dominated process for both sub -and super-saturated water vapor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the question of identifying the most relevant temperature for soot burn-off, oxidation of soot is a complex process due to their heterogeneous and versatile structure. Indeed, the chemical composition of soot emitted during fires can vary from organic to elemental carbon and the soot particle themselves can adsorb at their surface different kinds of complex organic molecules and even water ones (Lintis et al, 2021). Despite their complex nature, soot particles oxidation is generally assumed to produce mostly CO2, CO and H2O.…”
Section: Introductionmentioning
confidence: 99%